High-Order Sliding Mode Control of Greenhouse Temperature - H. Oubehar; A. Ed-Dahhak; A. Selmani; M. Outanoute; A. Lachhab; M. Guerbaoui; M.H. Archidi; B. Bouchikhi (Institute of Advanced Engineering and Science, 2016)
This paper deals with the design and implementation of the high order sliding mode controller to control temperature greenhouse. The control objective aims to ensure a favorable microclimate for the culture development and to minimize the production cost. We propose performing regulation for the greenhouse internal temperature based on the second order sliding mode technique known as Super Twisting Algorithm (STA). This technique is able to ensure robustness with respect to bounded external disturbances. A successful feasibility study of the proposed controller is applied to maintien a desired temperature level under an experimental greenhouse. The obtained results show promising performances despite changes of the external meteorological conditions.